Trends in maternal mortality in a tertiary hospital in West Delhi - Mitra, Soma; Mahajan, Nidhi; Maheshwari, Shashi L. Kabra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of current study was to find out incidence, causes and complications leading to maternal deaths in a tertiary care hospital and possible prevention of maternal deaths. Methods: Individual records of all maternal deaths over a period of five years from January 2006 to December 2010 were studied and causes of death and avoidable factors in each case were studied. Results: Major causes of maternal deaths were same throughout the study. The causes of maternal deaths were Hemorrhage (19.21%), Sepsis (15.76%), PIH (12.80%), Jaundice (8.37%). Direct obstetric causes contributed to 65.51% of cases. Indirect causes of maternal death contributed to 45.81%. Anemia alone accounted for 26.1% deaths. Maternal Mortality Ratio (MMR) was 362.57/100000 live births. There were 31.03% referred cases and 44.8% cases were admitted to ICU. Unbooked cases accounted for 84.72% of maternal deaths and these were mostly uneducated. Conclusions: Interventions for reduction of MMR are regular antenatal care, risk screening, skilled personnel at childbirth, good transport facilities, family planning services and safe abortion services. These facilities not only reduce burden on tertiary hospitals but also help in improving maternal prognosis.